Population survey of attitudes and beliefs regarding organic, genetically modified, and irradiated foods. Issue 1 (March 2017) - Gwira Baumblatt, Jane A; Carpenter, L Rand; Wiedeman, Caleb; Dunn, John R; Schaffner, William; Jones, Timothy F
Background: Sales of organic foods are increasing due to public demand, while genetically modified (GM) and irradiated foods are often viewed with suspicion. Aim: The aim of this research was to examine consumer attitudes toward organic, GM and irradiated foods to direct educational efforts regarding their consumption Methods: A telephone survey of 1838 residents in Tennessee, USA was conducted regarding organic, GM, and irradiated foods. Results: Approximately half of respondents (50.4%) purchased organic food during the previous 6 months ('consumers'). The most common beliefs about organic foods by consumers were higher cost (92%), and fewer pesticides (89%). Consumers were more likely than non-consumers to believe organic food tasted better (prevalence ratio 3.6; 95% confidence interval 3.02–4.23). A minority of respondents were familiar with GM foods (33%) and irradiated foods (22%). Conclusion: Organic food consumption is common in Tennessee, but knowledge about GM and irradiated foods is less common. Consumer health education should emphasize the benefits of these food options, and the safety of GM and irradiated foods.